Aplikasi Latihan Mental Dalam Pembelajaran Gerak Untuk Meningkatkan Keterampilan Pada Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan - Lalu Moh Yudha Isnaini; Suryansah suryansah (Universitas Hamzanwadi, 2019)
Mental training involves seeing or feeling psychologically the appearance of a skill in motion learning without displaying physical skills. Mental exercise becomes effective as an aid to improve motion learning skills. Mental exercise works very well when used in combination with skill training, both based on neoromuscular and cognitive. Psychic training is an effective method of learning to prepare well-learned skills in sports and health physical education learning. Mental training can help a student do the exercises to learn a skill. Mental exercise works well when combined with physical exercise. People who have high levels of ability in psychic training have high abilities in motion learning so that both levels of ability are important in motion skills to get optimal results. DOI: 10.29408/porkes.v2i1.1451